TLR-induced secretion of novel cytokine IL-27 is defective in newly diagnosed type-2 diabetic subjects - Madhumitha, Haridoss; Mohan, Viswanathan; Babu, Subash; Aravindhan, Vivekanandhan (Cytokine (Philadelphia, Pa.), 2018)
Toll-like receptors (TLRs), the innate immune receptors, act as sentinels bridging both innate and adaptive arms of immunity. In the present study, we estimated TLR-induced secretion of IL-27, IL-12, IL-23, IL-8, IP-10, IL-17, IL-6 and TNF-α (by ELISA) and expression of Human Leukocyte Antigen- (Human Leukocyte Antigen - antigen D Related (HLA-DR), CD69, CD80 (also known asB7-1) (by flowcytometry) and Activating Transcription Factor 3(ATF3) (by qRT-PCR) in whole blood cultures of control and type-2 diabetic (both newly diagnosed/NDD and known/KDM) subjects. TLR-induced secretion of IL-27 was significantly reduced in the NDD group compared to the control (Normal Glucose Tolerance (NGT)) and KDM groups. On the other hand, the expression of CD80 was significantly upregulated in both the monocytes and B cells in KDM group. This was associated with increased T cell activation (CD3+CD69+HLA-DR+) with increased IL-17 and reduced TNF-α secretion in this group. Impaired TLR-induced IL-27 secretion and augmented expression of antigen presentation molecules result in chronic T cell activation which may fuel T cell-mediated inflammation in type-2 diabetes.